(untitled) (Siddhajyoti Interdisciplinary Journal, 2026)
Parental involvement in their children’s education has a great impact on the child’s success. Involving parent’s efforts, teacher collaboration, and administrative support can improve the academic success of children. The study explored the lived experiences and challenges of parents from socioeconomically disadvantaged rural areas of Nepal in supporting their children’s education. The study used a qualitative design, interviewing nine parents in rural Gorkha to understand their views on participating in their children’s education. Facts and information have been given to a thematic analysis through the method of narrative inquiry. Two different narratives of parental involvement were found through an extensive examination of the data. One is optimistic narrative that showed parents’ confidence in children’s schools and their dedication to offering their children a better future, and other is a narrative of frustration that showed frustration resulting from a number of factors, such as parents’ socioeconomic status, fears about schools, and the influence of local social norms. It was evident that, despite challenges, parents viewed education as a means for their children’s success and strongly desired their school attendance. By uncovering and highlighting all of the context-related challenges the parents experienced the findings enrich the recognition of parents’ involvement in their children’ schooling in rural, impoverished geographical areas.